Eliminating Xenoantigen Expression on Swine RBC. Issue 3 (March 2017) - Wang, Zheng-Yu; Martens, Gregory R.; Blankenship, Ross L.; Sidner, Richard A.; Li, Ping; Estrada, Jose L.; Tector, Matthew; Tector, A. Joseph
Abstract : Background: The rapidly improving tools of genetic engineering may make it possible to overcome the humoral immune barrier that prevents xenotransplantation. We hypothesize that levels of human antibody binding to donor tissues from swine must approximate the antibody binding occurring in allotransplantation. It is uncertain if this is an attainable goal. Here we perform an initial analysis of this issue by comparing human antibody binding to red blood cells (RBC) isolated from knockout swine and to allogeneic or autologous human RBC. Methods: Human sera were incubated with RBC isolated from various genetically engineered swine or from humans. The level of IgG and IgM binding to these cells were compared using either flow cytometry or a novel mass spectrometric assay. Results: Mass spectroscopic quantitation of human antibody binding demonstrated that as few as 3 gene inactivations can reduce the levels human antibody binding to swine RBC that is as low as autologous human RBC. Flow cytometry showed that RBC from 2-gene knockout swine exhibited less human antibody binding than human blood group O allogeneic RBC in 22% of tested sera. Deletion of a third gene from pigs resulted in 30% of human samples having less IgG and IgM RBC xenoreactivity than alloreactivity. Conclusions: Xenoantigenicity of swine RBC can be eliminated via gene disruption. These results suggest that the gene knockout approach may be able reduce antigenicity in other pig tissues to levels that enable the xenotransplantation humoral barrier to be overcome. Abstract : Mass spectroscopic quantification is used to show that the disruption of GGTA1, CMAH and A4GalNT2 genes results in the near complete elimination of glycans on swine erthrocytes that are recognized by IgM and IgG in human sera. Supplemental digital content is available in the text.